Transcriptome profiling and RNA-Seq SNP analysis of reniform nematode (Rotylenchulus reniformis) resistant cotton (Gossypium hirsutum) identifies activated defense pathways and candidate resistance genes - Wubben, Martin J.; Khanal, Sameer; Gaudin, Amanda G.; Callahan, Franklin E.; McCarty, Jack C.; Jenkins, Johnie N.; Nichols, Robert L.; Chee, Peng W. (Frontiers in Plant Science, 2025)
The reniform nematode (Rotylenchulus reniformis Linford & Oliveira) is a serious pathogen of Upland cotton (Gossypium hirsutum L.) wherever it is grown throughout the United States. Upland cotton resistance to R. reniformis derived from the G. barbadense accession GB713 is largely controlled by the Renbarb2 locus on chromosome 21. Renbarb2 has proven useful as a tool to mitigate annual cotton yield losses due to R. reniformis infection; however, very little is known about the molecular aspects of Renbarb2-mediated resistance and the gene expression changes that occur in resistant plants during the course of R. reniformis infection. In this study, two nearly isogenic lines (NILs), with and without the Renbarb2 locus, were inoculated with R. reniformis and RNAs extracted and sequenced from infected and control roots at 5-, 9-, and 13-dai (days after inoculation). A total of 966 differentially expressed genes (DEGs) were identified in the resistant NIL while 133 DEGs were discovered from the susceptible NIL. In resistant plants, biological processes related to oxidation-reduction reactions and redox homeostasis were enriched at each timepoint with such genes being up-regulated at 5- and 9-dai but then being down-regulated at 13-dai. DEGs associated with cell wall reinforcement and defense responses were also up-regulated at early timepoints in resistant roots. In contrast, in susceptible roots, defense-related gene induction was only present at 5-dai and was comprised of far fewer genes than in the resistant line. ERF, WRKY, and NAC transcription factor DEGs were greatly enriched at 13-dai in resistant roots but were absent in the susceptible. Cluster analysis of resistant and susceptible DEGs revealed an ‘early’ and ‘late’ response in resistant roots that was not present in the susceptible NIL. SNP analysis of transcripts within the Renbarb2 QTL interval identified five genes having non-synonymous mutations shared by other Renbarb2 germplasm lines. The basal expression of a single candidate gene, Gohir.D11G302300, a CC-NBS-LRR homolog, was ~3.5-fold greater in resistant roots versus susceptible. These data help us to understand the Renbarb2-mediated resistance response and provides a short list of candidate resistance genes that potentially mediate that resistance.